Interdisciplinary perspectives on accessing specialty evidence-based treatment for Medicaid-insured adolescents with eating disorders - Peyton Crest; Siena S. Vendlinski; Renee Borges; John Landsverk; Erin C. Accurso (Journal of Eating Disorders)
Abstract Background Family-based treatment (FBT), the leading intervention for adolescents with anorexia nervosa (AN), is severely understudied in outpatient care settings that serve publicly-insured populations. Many individuals with public insurance are lower-income, racially and ethnically diverse, and experience barriers to accessing evidence-based interventions for eating disorders (EDs). Methods Semi-structured interviews were conducted with ten interdisciplinary providers who provide specialty care to youth with EDs in an inpatient and/or outpatient medical setting. Interview questions were focused on the interdisciplinary providers’ experiences of caring for individuals with EDs, with a focus on differences in care for those with private insurance compared to public insurance. The interviews took place two years after training in FBT was delivered to mental health providers in San Francisco County, which created opportunities to explore provider perspectives on collaborating with newly-trained mental health providers in the community implementing FBT with publicly-insured youth. Results Content analysis converged on three themes: the critical importance of supporting mental health treatment within the context of medical care, complex challenges when helping patients and their families navigate publicly-funded health care systems, and the overall positive impact of the FBT rollout in San Francisco County. Participants emphasized greater confidence in patient outcomes when collaborating with FBT providers and noted discord when working with providers not trained in EDs or FBT. Referral systems, weight-based stigma, and a lack of appropriate services were highlighted as significant barriers to care. To facilitate treatment engagement in publicly-insured populations, participants stressed the importance of clinicians providing psychoeducation and providing services with a high degree of cultural competence. Participants expressed that patients’ ability to access FBT and providers’ ability to collaborate on cases markedly improved following the county training, increasing their sense of efficacy in delivering adequate patient care. Conclusions The discussed themes highlight the importance of access to FBT for individuals in underserved communities, which can significantly reduce both provider and patient burden. Despite various barriers to utilizing FBT in publicly-funded settings, clinicians stressed that cultural adaptations increase the implementation of and facilitate family engagement in FBT, which is consistent with previous literature examining evidence-based intervention implementation science.